Your Care Mitigates My Ego Depletion: Why and When Perfectionists Show Incivility Toward Coworkers - Hussain, Muhammad Ali; Chen, Lu; Wu, Lusi (Frontiers in Psychology, 2021)
Drawing on ego depletion theory and trait activation theory, this study examines why and when employee perfectionism personality is linked with incivility toward coworkers. The study indulges ego depletion as a mediator between perfectionism personality and incivility toward coworkers, with coworker empathic concern moderating the relationship between perfectionism personality and ego depletion. A three-waved questionnaire was incorporated with sample of 253 employee-coworker dyads. Our findings demonstrate that dimensions of perfectionism personality are positively associated with incivility toward coworkers. In addition, our study confirms that ego depletion mediates the relationship between self-oriented perfectionism, other-oriented perfectionism, and incivility toward coworkers. Furthermore, our study shows that high levels of coworker empathic concern weakens the direct effect of self-oriented perfectionism on ego depletion along with the indirect effect of self-oriented perfectionism on incivility toward coworkers. Theoretical and practical implications of the study are discussed in the organizational context.